P105 Safety, Feasibility And Quality Of Sputum Induction In Preschool Children With Obstructive Airways Disease. (10th November 2014) - Robson, K; Nagakumar, P; Collins, N; Davies, JC; Fleming, L; Balfour-Lynn, I; Rosenthal, M; Hogg, C; Jochmann, A; Bush, A; Saglani, S
Abstract : Introduction: Airway infection and inflammation in infancy and preschool years contribute to the pathogenesis of cystic fibrosis (CF), severe wheezing and recurrent cough. However, the use of sputum induction (SI) to guide management in preschool children with obstructive airways disease remains under-explored. We hypothesised that SI can be performed safely in preschool children with obstructive airways disease, and that samples of sufficient quality to assess infection and inflammation can be obtained. Methods: SI was performed using nebulised hypertonic saline, 3.5% if there was a history of wheeze or 7% if the child had no wheeze or a diagnosis of CF. The procedure was undertaken for 15 min and safety was assessed using pulse-oximetry and auscultation. Physiotherapy, followed by a cough/oropharyngeal swab (CS), and oropharyngeal suction (OS) were undertaken to obtain samples. All samples were analysed for bacterial culture and viral PCR, a sub-set were processed for cytology. Results: 35 children (16 males), median age 32 months (range 7–70 months) were included. 32/35 (91%) completed the procedure. The remaining three did not complete nebulisation as they became too upset, but underwent sample collection. None of the patients had any drop in oxygen saturation or increased respiratory symptoms. 16/35 (46%) patients had positive pathogen identification (22 separate bacterial or viral isolates) from SI samples obtained by OS. Only 3/35 (9%) positive isolates were identified from CS. 29/35 samples were able to be processed for cytology (see Table 1) Conclusions: Performance of SI was safe, feasible and well tolerated by preschool children with a range of obstructive airways diseases. Pathogen identification was significantly higher in samples obtained by OS compared to CS. Samples were of sufficient quality for cytological analysis in approximately half the patients. Future work will determine the clinical utility of SI as a non-invasive sample to guide therapy in preschool obstructive airways disease.